2006
DOI: 10.1148/radiol.2402050223
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease: Clinical and Cost Comparisons between Duplex US and Contrast-enhanced MR Angiography—A Multicenter Randomized Trial

Abstract: Replacing duplex US with contrast-enhanced MR angiography for the initial imaging work-up of patients with PAD reduces the need for additional imaging, although diagnostic costs are higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 35 publications
0
14
0
4
Order By: Relevance
“…A prospective multicenter trial of patients318 randomized to either CE-MRA or duplex ultrasound for PAD evaluation found the results of both studied to have similar ability to predict changes in disease severity and quality of life. Importantly, patients that received peripheral CE-MRA experienced a reduction of additional vascular imaging procedures by 42%.…”
Section: Important Applicationsmentioning
confidence: 99%
“…A prospective multicenter trial of patients318 randomized to either CE-MRA or duplex ultrasound for PAD evaluation found the results of both studied to have similar ability to predict changes in disease severity and quality of life. Importantly, patients that received peripheral CE-MRA experienced a reduction of additional vascular imaging procedures by 42%.…”
Section: Important Applicationsmentioning
confidence: 99%
“…38 Recent studies in Europe on patients being evaluated for peripheral arterial disease indicated that MR and CT provide higher cost alternatives to US due to the fewer number of reimaging studies sometimes required, but no differences were found in patient outcomes or quality of life. 39,40 US also provides an accurate assessment of peripheral vascular disease (PVD), especially in the setting of patients undergoing interventions. US is often superior to angiography and MR in this diagnosis, and the use of US provides lower costs and significantly shortens the patient's hospital stay.…”
Section: Vascularmentioning
confidence: 99%
“…The radiologic approach to the diagnosis of PAD has changed substantially in the past few years [6]. Typically the ankle-brachial index (ABI) is the first noninvasive imaging test performed in the investigation of PAD.…”
mentioning
confidence: 99%